2024
DOI: 10.1186/s12967-024-05089-8
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester inhibits neuro-inflammation and oxidative stress following spinal cord injury by mitigating mitochondrial dysfunction via the SIRT1/PGC1α/DRP1 signaling pathway

Yanan Zhang,
Qian Deng,
Hongxiang Hong
et al.

Abstract: Background The treatment of spinal cord injury (SCI) has always been a significant research focus of clinical neuroscience, with inhibition of microglia-mediated neuro-inflammation as well as oxidative stress key to successful SCI patient treatment. Caffeic acid phenethyl ester (CAPE), a compound extracted from propolis, has both anti-inflammatory and anti-oxidative effects, but its SCI therapeutic effects have rarely been reported. Methods We cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…Metabolites of various natural products exhibit antitumor effects in cancers [12][13][14][15] . Caffeic acid phenethyl ester (CAPE), one of the main active ingredients of propolis, was originally considered to be an inhibitor of NF-κB, and has since been discovered to possess antiviral, antibacterial, anticancer, and immunomodulatory properties [16][17][18][19] . Numerous studies have demonstrated the potential of CAPE as a chemosensitizer in conjunction with chemotherapy agents [20][21][22] .…”
mentioning
confidence: 99%
“…Metabolites of various natural products exhibit antitumor effects in cancers [12][13][14][15] . Caffeic acid phenethyl ester (CAPE), one of the main active ingredients of propolis, was originally considered to be an inhibitor of NF-κB, and has since been discovered to possess antiviral, antibacterial, anticancer, and immunomodulatory properties [16][17][18][19] . Numerous studies have demonstrated the potential of CAPE as a chemosensitizer in conjunction with chemotherapy agents [20][21][22] .…”
mentioning
confidence: 99%